2019
DOI: 10.1038/s41598-019-48939-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of addition of adjuvants on physical and chemical characteristics of Bt bioinsecticide mixture

Abstract: Bacillus thuringiensis (Bt) is the main bacterium used in the formulation of bioinsecticides because it produces toxins and spores that are toxic to several orders of insects. The efficacy of Bt bioinsecticide is influenced by the quality of its application. The association with other crop protection products, such as adjuvants, can affect the physical and chemical parameters of the mixture. This study evaluated the physical and chemical parameters, volume median diameter (VMD), uniformity coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…In the present study, higher vegetative growth and sporulation were observed following treatment with the mixture containing Bt biopesticide and LI. The pH ranged from 3.5 for the WP formulations to 4 for the SC formulations 21 , indicating that a pH below 5 does not affect the vegetative growth of colonies and number of spores.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, higher vegetative growth and sporulation were observed following treatment with the mixture containing Bt biopesticide and LI. The pH ranged from 3.5 for the WP formulations to 4 for the SC formulations 21 , indicating that a pH below 5 does not affect the vegetative growth of colonies and number of spores.…”
Section: Discussionmentioning
confidence: 99%
“…Although pH is not considered the key determinant of Bt colony growth and sporulation, spore germination was substantially reduced in acidic media with a pH up to 5.0 21 , 32 , whereas spore germination was completely inhibited due to protein solubilization in alkaline media with a pH above 8 33 . In the present study, higher vegetative growth and sporulation were observed following treatment with the mixture containing Bt biopesticide and LI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Eucalyptus grandis plants subject to P deficiency absorbed more 14 C-glyphosate 12 . These divergences may be associated with the physical–chemical characteristics of the spray solution, since the electrical conductivity, pH, surface tension and viscosity can interfere in the droplet spectrum and influence the interaction of the herbicide with the target surface 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%